SLA-Printed BaTiO3-Reinforced Bio-Nanocomposites: Influence of Printing Parameters on Mechanical, Dielectric, and Thermal Properties - Mahouti, Tarlan; Ornek, Ece; Cevir, Beste; Berber, Hale; Belen, Mehmet Ali; Sadikoglu, Hasan; Yilmazer, Hakan (AMER CHEMICAL SOC, 2025)
The development of biocompatible nanocomposites with enhanced dielectric behavior has gained significant importance in medical electronics, particularly for high-frequency applications. This study presents the fabrication of barium titanate (BaTiO3)-reinforced nanocomposites using a photopolymer bioresin and stereolithography (SLA) 3D printing. Nanocomposites were prepared with 0.5, 1.0, and 1.5 wt % BaTiO3 concentrations and printed using a Creality HALOT R6 SLA printer. Postprocessing involved support removal, isopropyl alcohol cleaning, and UV curing for 120 s on both sides. Dielectric measurements were performed using a Vector Network Analyzer (VNA) in the 1-20 GHz range, where the dielectric constant of the pure resin was found to be approximately 3.06, but unexpectedly decreased to similar to 2.58 at 1.0 wt % BaTiO3 (attributed to the low filler fraction limiting polarization). The loss tangent remained below 0.05 across the range, supporting low-loss characteristics. SEM-EDS analysis confirmed uniform filler dispersion without visible agglomeration. FTIR spectroscopy indicated the successful incorporation of BaTiO3 into the polymer matrix. Thermal analysis showed slightly enhanced stability, while mechanical testing revealed an increase in tensile strength from 25.3 MPa (neat resin) to 27.6 MPa for the 1.0 wt % nanocomposite. The combined results validate that BaTiO3-reinforced SLA-printed nanocomposites can meet the dielectric and mechanical performance requirements of GHz-range medical sensors without sacrificing print resolution or biocompatibility.
Keywords: BARIUM-TITANATE; POLYMER NANOCOMPOSITES; STEREOLITHOGRAPHY; BATIO3; RESINS; OIL; Chemistry